Recruiting hospitalized patients for research: How do participants differ from eligible nonparticipants?. Issue 4 (5th April 2013) - Voss, Rachel; Gravenstein, Stefan; Baier, Rosa; Butterfield, Kristen; Epstein‐Lubow, Gary; Shamji, Hannah; Gardner, Rebekah
<x xml:space="preserve">Abstract</x> BACKGROUND Randomized controlled trials provide strong evidence for guidelines and interventions. Yet, much of the eligible population declines to be studied. OBJECTIVE To identify differences between participants and eligible nonparticipants in (1) perceived stress, (2) self‐efficacy, (3) recovery expectations, (4) discussing advance directives, and (5) understanding a standard prescription label (health literacy). DESIGN Quasi‐experimental prospective cohort study in 5 acute‐care hospitals. METHODS We approached 295 hospital inpatients as they were being recruited for a behavioral intervention and asked them to answer 5 screening questions. We matched respondents' answers to their acceptance of the behavioral intervention and to Medicare claims and enrollment data. We used multivariate logistic regression to compare consent rates based on screening‐question responses. SETTING/PATIENTS Hospitalized fee‐for‐service Medicare patients. RESULTS Patients were less likely to consent to the behavioral intervention when they reported feeling unable to control important things in their lives (odds ratio [OR]: 0.35, 95% confidence interval [CI]: 0.14‐0.92), had low recovery expectations (OR: 0.17, 95% CI: 0.06‐0.45), or were confused by any question (OR: 0.11, 95% CI: 0.05‐0.24). Conversely, individuals who answered the medication question incorrectly were more likely to consent to the behavioral intervention (OR: 3.82, 95% CI: 1.12‐13.03). There were no significant differences in consent for patients who reported feeling overwhelmed or reported discussing advance care planning with family members or doctors. CONCLUSIONS Hospitalized eligible nonparticipants differ in constructs related to perceived stress, recovery expectation, and health literacy. Recognizing such characteristics may inform strategies to improve intervention recruitment in the hospital and representation in clinical trials. Journal of Hospital Medicine 2013;8:208–214. © 2013 Society of Hospital Medicine